IMPLEMENTING ONLINE LEARNING IN THE COVID-19 PANDEMIC - Ratih Septiani; Murtono; Erik Aditia Ismaya (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to analyze the preparation of online learning during the pandemic at SD N Panjunan 02 Pati and to analyze the implementation of online learning during the pandemic at SD N Panjunan 02 Pati. This study discussed the plan and implementation of online learning. Online learning referred to teaching students separately from the teachers and the learning was performed through internet and online learning resources according to information and communication technology and the help of sophisticated media. This research was a qualitative descriptive study conducted at SDN Panjunan 02 Pati with the research subjects of students, teachers and parents. The object of this study was online learning in which the data were collected through observation, interviews, and documentation. The data were analyzed through descriptive qualitative data analysis. The results showed that at the planning stage, there were several things that had been prepared for online learning at SDN Panjunan 02, namely objectives, time, strategies, constraints and solutions in planning distance learning. At the implementation stage, there were several things, namely the schedule of online learning activities, how to implement online learning, constraints and solutions for implementing online learning, and the motivation in online learning. From the results of this study, it was concluded that SDN Panjunan 02 has prepared and implemented the learning process well to deal with the current pandemic.